Enhancement of Executive Functions but Not Memory by Multidomain Group Cognitive Training in Patients with Parkinson's Disease and Mild Cognitive Impairment: A Multicenter Randomized Controlled Trial. (30th November 2020) - Kalbe, Elke; Folkerts, Ann-Kristin; Ophey, Anja; Eggers, Carsten; Elben, Saskia; Dimenshteyn, Karina; Sulzer, Patricia; Schulte, Claudia; Schmidt, Nele; Schlenstedt, Christian; Berg, Daniela; Witt, Karsten; et al.
Abstract : Background . Meta-analyses have demonstrated cognitive training (CT) benefits in Parkinson's disease (PD) patients. However, the patients' cognitive status has only rarely been based on established criteria. Also, prediction analyses of CT success have only sparsely been conducted. Objective . To determine CT effects in PD patients with mild cognitive impairment (PD-MCI) on cognitive and noncognitive outcomes compared to an active control group (CG) and to analyze CT success predictors. Methods . Sixty-four PD-MCI patients (age: 67.61 ± 7.70; UPDRS-III: 26.58 ± 13.54; MoCA: 24.47 ± 2.78) were randomized to either a CT group or a low-intensity physical activity CG for six weeks (twice weekly, 90 minutes). Outcomes were assessed before and after training. MANOVAs with follow-up ANOVAs and multiple regression analyses were computed. Results . Both interventions were highly feasible (participation, motivation, and evaluation); the overall dropout rate was 4.7%. Time × group interaction effects favoring CT were observed for phonemic fluency as a specific executive test (p = 0.018, η p 2 = 0.092 ) and a statistical trend for overall executive functions (p = 0.095, η p 2 = 0.132 ). A statistical trend for a time × group interaction effect favoring CG was shown for the digit span backward as a working memory test (p = 0.098, η p 2 = 0.043 ). Regression analyses revealed cognitive baseline levels, education, levodopa equivalent daily dose, motor scores, and ApoE status as significant predictors for CT success. Conclusions . CT is a safe and feasible therapy option in PD-MCI, yielding executive functions improvement. Data indicate that vulnerable individuals may show the largest cognitive gains. Longitudinal studies are required to determine whether CT may also attenuate cognitive decline in the long term. This trial is registered with DRKS00010186.